The Effect of Standard and Beveled Heels of Orthopedic Shoe on Vertical Ground Reaction Forces during Walking in Healthy Subjects - a'aliyeh Daryabor; Hassan Saeedi; Meria Yazdani; Mohammad Sadegh Ghasemi; Hoda Nabavi; Afsaneh Mohammadpour; Mohammad Kamali (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: in normal walking, repetitive vertical ground reaction forces are tansformed on musculo-skeletal system. Magnitude of force during impact is major contributor to overuse injuries. Purpose of this study was the evaluate to effect of standard and beveled heel at orthopedic shoe on vertical ground reaction forces during walking in healthy subjects. Materials & Methods: 30 healthy adults (12 male, 18 female) participated in this study by simple impossible sampling. Subjects walked along an 8-m walkway in three different conditions: barefoot, orthopedic shoe with standard heel and orthopedic shoe with beveled heel. Vertical ground reaction force data collected in initial stance phases of walking using Kistler force plate. Results: Results of this study showed significant increasing in impact force in barefoot compared with orthopedic shoe with standard and beveled heels (P˂0.0001). First peak of vertical force and loading rate showed significant reduction in orthopedic shoe with beveled heel compared with orthopedic shoe with standard heel (P˂0.05). Conclusion: using the beveled heel by changing the location of the ground reaction force from the ankle joint axis, facilitated first rocker and reduce first peak of vertical force and loading rate. because of complication of deleterious loads on lower limb during walking, we could use of this type of heel for some of the patient with special orthopedic disease.